Peningkatan Hasil Belajar Terpadu Siswa Menggunakan Problem-Based Learning Berbantuan Media Powtoon di Kelas V Sekolah Dasar - Muzakki, Adib; Arwin, Arwin (Universitas Negeri Padang, 2023)
This research was conducted because in integrated thematic learning, students' learning outcomes are very low. The research aims to describe the use of the Problem-Based Learning model in the learning process to improve learning outcomes. The research was conducted in 2 cycles. The four stages in the research procedure consist of planning, implementation, observation and reflection. Observation sheets, test sheets and non-tests are instruments for data collection. The results showed an increase in a) RPP cycle I 81.9% sufficient qualifications and cycle II 94% very good qualifications, b) Implementation of the learning process aspects of teachers and students cycle I 82% good qualifications and cycle II 96% very good qualifications, c) The results of the assessment of students in improving learning outcomes in cycle I obtained an average of 76.5% sufficient qualifications and cycle II 85% very good qualifications. Thus, it can be concluded that the Powtoon-assisted PBL model can improve the learning outcomes of students in integrated thematic learning in class V.